IN THE PRESENT DAY, "EMPLOYING MUSIC ART" IS AN IMPORTANT DIMENSION IN HIGHER EDUCATION: वर्तमान समय में “रोजगार युक्त संगीत कला” उच्चशिक्षा में एक महत्वपूर्ण आयाम - Jain, Lata (International Journal of Research -GRANTHAALAYAH, 2015)
The music tradition in India is very ancient. Music has been related to life in any field, be it Indian or Western, since time immemorial. It is a fine art in which the musician expresses his feelings through tone, rhythm, rhythm. Music has the power to make the entire human world self-reliant, this is an art that is loved by everyone in the world. There is no place in the world where people are not involved in music, so Bhartrihari has treated a music-less human like an animal without horns and tail. भारत में संगीत परम्परा बहुत प्राचीन है। संगीत किसी भी क्षेत्र का हो, चाहे भारतीय हो अथवा पाश्चात्य, आदिकाल से ही उसका जनजीवन से संबंध रहा है। यह एक ऐसी ललित कला है जिसमें संगीतज्ञ स्वर, लय, ताल के माध्यम से अपने मनोभावों को व्यक्त करता है। संगीत में सम्पूर्ण मानव जगत को आत्मविभोर करने की शक्ति होती है यह ऐसी कला है जो विश्व में सभी को प्रिय है। संसार की कोई भी ऐसी जगह नहीं है जहाँ के लोग संगीत से जुड़े न हांे, इसलिए भर्तृहरि ने संगीत विहीन मानव को बिना सींग और पूँछ वाले पशु के समान माना है।